Role of Algerian Diplomacy to Keep pace and security in the territorial region known by african sahel - Melouki, Slimane (revue mofakir, 2018)
The Algerian authorities desired to be firmly integrated into the new North-South security system. The country found its way to emerge from its diplomatic isolation through a rapprochement with the United States on the security level. The results have undoubtedly been beneficial for Algiers, which has now become a new partner for Washington in the “Global War on Terror” . This article tray to explain or clarify The Algerian diplomacy position or role in the territorial region known as “Sahel” in order to Keep pace and security in the Malian state in terms to preserve the Malian sovereignty and security according the international law principles. Key words: Algerian Diplomacy, geopolitical framework, territorial region, exit strategy, current changes, maintain position, regional security matters.